Failure Estimates for SiC Power MOSFETs in Space Electronics - Galloway, Kenneth F.; Witulski, Arthur F.; Schrimpf, Ronald D.; Sternberg, Andrew L.; Ball, Dennis R.; Javanainen, Arto; Reed, Robert A.; Sierawski, Brian D.; Lauenstein, Jean-Marie (Aerospace, 2018)
Silicon carbide (SiC) power metal-oxide-semiconductor field effect transistors (MOSFETs) are space-ready in terms of typical reliability measures. However, single event burnout (SEB) due to heavy-ion irradiation often occurs at voltages 50% or lower than specified breakdown. Failure rates in space are estimated for burnout of 1200 V devices based on the experimental data for burnout and the expected heavy-ion linear energy transfer (LET) spectrum in space.